The differences in functional recovery between patients with stroke who are HIV positive and those who are HIV negative - Janse van Rensburg, Jenny (My University, 2015)
Stroke is a significant contributor to disease worldwide and is the second highest cause of death in both men and women. Importantly, stroke is not only a common cause or mortality but also morbidity. This increased risk of suffering a stroke could lead to an increased number of individuals with functional limitations. The main objective in stroke rehabilitation is seen as aiding the patient to achieve their highest physical and psychological performance, with the ultimate goal of a stroke survivor being one of functional independence allowing them to return to their home and reintegrate into their community. The aim of this study is to describe the differences in functional abilities between patients with stroke who are HIV positive and those who are HIV negative admitted to Witrand rehabilitation unit in the North-West province of South Africa. This is a retrospective longitudinal study utilizing the review of subject records. All subject files dating back to 21 April 2005 to December 2010 were analysed. Functional ability of patients with stroke was scored using the Beta assessment tool.The Beta assessment tool is one of three platform level tools designed by the South African Database for Functional Medicine (SADFM).It is an evidence – based scoring system which can convert a patient’s functional abilities and behaviour into quantifiable data. Scores on admission and discharge were recorded to determine the presence of change in functional ability after having received rehabilitation. Demographic information and clinical characteristics of subjects were captured using a self-designed questionnaire. Data were analysed using both a two sample t-test and descriptive statistical tests. Over the period, 2005 – 2010, 173 stroke survivors were admitted to the Witrand rehabilitation unit.Data from 32 patient files was excluded for not meeting the inclusion criteria; leaving data from 141 files to form our study group (n). The study group included 53.2% male and 46.8% female stroke survivors, with the mean age for stroke at 54.4 years and52.4 years for males and females respectively. Ischaemic strokes were more prevalent than haemorrhagic strokes (74.5% and 25.5% respectively) with hypertension asthe most common (31.9%) stroke risk factor. The mean age of stroke onset for a HIV positive individual was 39.6 years and 54.9 years for an individual without HIV.This study found that HIV positive individuals required on average 7.5 days less to rehabilitate than an individual with HIV. This discrepancy could be a result of the notably younger HIV positive group. After receiving rehabilitation from a multidisciplinary team, the HIV positive group improved with an average of 40 points and the individuals without HIV by 38 points. When performing the various statistical tests there were in fact no significant differences between the two different clinical groups. Despite the statistically insignificant findings when comparing the HIV positive and HIV negative group, when taking a closer look at the study groups demographics and clinical characteristics this study yielded interesting results. It could be argued that a majority of the HIV positive group were generally younger than the HIV negative group and perhaps the advantage of age on recovery could result in this group in gaining, on average, a similar number of points on the beta scale with those individual without HIV.Prior to their commencement of rehabilitation it should be taken into account that neurological recovery requires a degree of brain reorganization and that with age comes a certain degree of neuronal loss. Neuroplasticity is the ability of the central nervous system to respond to internal and external stimuli by reorganizing its structure, function and connections. Normal ageing is associated with a decline in and reduced plasticity. These negative changes can be experienced as reductions in processing speed, working memory and peripheral nervous system functions; all of which can be associated with poorer rehabilitation outcomes. Neural plasticity is crucial for functional recovery and this occurs more effectively and efficiently in younger individuals.However, in general the age for stroke onset was younger than that of developed countries thus stroke should no longer be considered an ‘old-age’ disease in developing countries. Keywords: Stroke; Human Immunodeficiency Virus (HIV); Functional abilities
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Physiotherapy Johannesburg, 2014
Keywords: Stroke--therapy; HIV--complications